Music, politics, and the nation at the Cultural Center of the Philippines - Castro, Christi-Anne Salazar (2001)
This dissertation examines the relationship between music and politics at the Cultural Center of the Philippines (CCP) between 1969 and 2001. Mandated to preserve, develop, and promote national culture in the Philippines, the CCP has been embroiled in politics since it was founded it 1969 for a number of reasons-not to least of which was its patronage by Imelda Marcos, the infamous wife of the dictator Ferdinand Marcos. This dissertation reconstructs the history of the institution with information from ethnographic interviews, periodicals, and other sources (and at times contrasts it with the Philippine Center in New York) while making a commentary on how music production at the Center has both reflected and promoted different ideologies of identity and nation. From a mentality of the early years in which Western culture dominated ideas about art to the Filipization and democratization of the Center following the People Power Revolution of 1986, the CCP has been a place of both tradition and dynamic creativity.